Answer:
D) x = 4, y = -2, z = 3
Step-by-step explanation:
x = 3z − 5
2x + 2z = y + 16
2(3z - 5) + 2z = y + 16
6z - 10 + 2z = y + 16
8z = y + 26 ---> (A)
7x − 5z = 3y + 19
7(3z - 5) - 5z = 3y + 19
21z - 35 - 5z = 3y + 19
16z = 3y + 54 ---> (B)
8z = y + 26
16z = 3y + 54
2(y + 26) = 3y + 54
2y + 52 = 3y + 54
y = -2
8z = -2 + 26
8z = 24
z = 3
x = 3(3) - 5
x = 4
Add like terms
-4x+x=-3x
6-2=4
So the simplified term is 4-3x
Answer:
C
Step-by-step explanation:
Given
6(x + 4) = 2(y + 5) ← distribute parenthesis on both sides of the equation
6x + 24 = 2y + 10 ( subtract 10 from both sides )
6x + 14 = 2y ( divide all terms by 2 )
3x + 7 = y, hence
y = 3x + 7 → C
Answer: D) x = 8
Step-by-step explanation: In order to get this answer, you need to keep the 236 and add 59 evry time until you get 708.
Another thing is to multiply 59 by 8, which will give you 472. Now we add 472 and 236 and we get 708.
59 x 8 = 472 + 236 = 708.
56 + 56 + 56 + 56 + 56 + 56 + 56 + 56 = 472 + 236 = 708.
Hope this helped!
Plz mark brainliest!